2021
DOI: 10.1021/acs.molpharmaceut.1c00468
|View full text |Cite
|
Sign up to set email alerts
|

Improving Dermal Delivery of Rose Bengal by Deformable Lipid Nanovesicles for Topical Treatment of Melanoma

Abstract: Cutaneous melanoma is one of the most aggressive and metastatic forms of skin cancer. However, current therapeutic options present several limitations, and the annual death rate due to melanoma increases every year. Dermal delivery of nanomedicines can effectively eradicate primary melanoma lesions, avoid the metastatic process, and improve survival. Rose Bengal (RB) is a sono-photosensitizer drug with intrinsic cytotoxicity toward melanoma without external stimuli but the biopharmaceutical profile limits its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“… 63–66 In the case of RB, increased cellular uptake seems to be critical for phototoxic activity: regardless of the level of singlet oxygen generation, RB-loaded dendrimersomes generate significantly higher levels of intracellular ROS, which translates into a stronger phototoxic effect. The IC 50 values for RB-loaded dendrimersomes in vitro are remarkably low (~1 µM RB for both formulations), considerably lower than those for most formulations mentioned above (for instance 28 , 30 , 32 , 36 ). Importantly, the dark toxicity of RB-loaded dendrimersomes is negligible in the concentration range used.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 63–66 In the case of RB, increased cellular uptake seems to be critical for phototoxic activity: regardless of the level of singlet oxygen generation, RB-loaded dendrimersomes generate significantly higher levels of intracellular ROS, which translates into a stronger phototoxic effect. The IC 50 values for RB-loaded dendrimersomes in vitro are remarkably low (~1 µM RB for both formulations), considerably lower than those for most formulations mentioned above (for instance 28 , 30 , 32 , 36 ). Importantly, the dark toxicity of RB-loaded dendrimersomes is negligible in the concentration range used.…”
Section: Discussionmentioning
confidence: 60%
“…A promising way to increase bioavailability of RB is to deliver it in nanoformulations. 8 To date, various types of RB-loaded nanocarriers have been designed for skin cancer PDT in vitro and in vivo, including lipid-based formulations 28–30 polymeric nanoparticles, 31–33 upconversion nanoparticles, 34 , 35 inorganic nanoparticles 36 and so on.…”
Section: Discussionmentioning
confidence: 99%
“…UV analysis was employed for the RB quantification. Evaluation of RB content in PBS buffer (pH 7.4), used for both the determination of the drug content (Section 2.4) and in vitro drug release studies (Section 2.5), was carried out with a UV spectrophotometer (Shimadzu UV-1800, Kyoto, Japan) (λ = 549 nm) [12]. RB concentrations were calculated by interpolation of the calibration curve prepared in PBS buffer (pH 7.4).…”
Section: Physical and Chemical Characterization Of Microspheresmentioning
confidence: 99%
“…In order to bypass antibiotic resistance phenomena, some new chemicals have been designed against multidrug resistant (MDR) strains and appear as suitable alternatives in late-stage clinical studies [11]. For this purpose, although rose bengal (RB) has been legally approved just as a dye for the diagnosis of ocular disorders, it has recently been explored for its unique activity against cancer [12] and infections [13]. Recently, a work published in collaboration with Provectus Biopharmaceuticals reported that RB was very effective, and as an antimicrobial drug in skin and soft tissue infections (SSTIs), associated with Gram-positive bacteria and MDR strains [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, RB demonstrated a broad spectrum of induced cytotoxicity against tumor and microbial cells [ 19 ]. In oncology, the main relevant applications of RB (namely PV-10, a 10% RB solution) were reported in the treatments of local and metastatic melanoma, both in the absence of external stimuli such as ultrasound and PDT stimuli [ 20 ]. In melanoma cells, RB was reported to induce death pathways as necrosis and caspase-dependent and-independent apoptosis [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%